Smooth muscle FGF/TGFβ cross talk regulates atherosclerosis progression - Pei‐Yu Chen; Lingfeng Qin; Guangxin Li; George Tellides; Michael Simons (EMBO Molecular Medicine)
Abstract The conversion of vascular smooth muscle cells (SMCs) from contractile to proliferative phenotype is thought to play an important role in atherosclerosis. However, the contribution of this process to plaque growth has never been fully defined. In this study, we show that activation of SMC TGFβ signaling, achieved by suppression of SMC fibroblast growth factor (FGF) signaling input, induces their conversion to a contractile phenotype and dramatically reduces atherosclerotic plaque size. The FGF/TGFβ signaling cross talk was observed in vitro and in vivo. In vitro, inhibition of FGF signaling increased TGFβ activity, thereby promoting smooth muscle differentiation and decreasing proliferation. In vivo, smooth muscle‐specific knockout of an FGF receptor adaptor Frs2α led to a profound inhibition of atherosclerotic plaque growth when these animals were crossed on Apoe−/− background and subjected to a high‐fat diet. In particular, there was a significant reduction in plaque cellularity, increase in fibrous cap area, and decrease in necrotic core size. In agreement with these findings, examination of human coronary arteries with various degrees of atherosclerosis revealed a strong correlation between the activation of FGF signaling, loss of TGFβ activity, and increased disease severity. These results identify SMC FGF/TGFβ signaling cross talk as an important regulator of SMC phenotype switch and document a major contribution of medial SMC proliferation to atherosclerotic plaque growth.